Mich. Rev. Stat., ch. 162, §16 (1846) - (:unkn) unknown (General Publisher, 1846)
Required any person going armed with any dirk, dagger, sword, pistol, or other offensive and dangerous weapon to post a surety once a complaint was filed, having cause to fear an injury or breach of the peace. Surety not to exceed six months with appeals provided.
--
Keywords: POSSESSION - DANGEROUS PERSONS